Pengaruh kualitas pelayanan terhadap kepuasan pasien rawat inap BPJS - Nurwan Alkahfi; Dwi Noerjoedianto; Andi Subandi; Asparian Asparian; Willia Novita Eka Rini; Muldiasman Muldiasman (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Service quality is a key determinant of patient satisfaction in hospital settings, particularly for National Health Insurance (BPJS) participants. Raden Mattaher Hospital Jambi, as a referral hospital, experiences increasing BPJS inpatient visits. However, complaints and fluctuations in satisfaction index indicate potential service quality gaps. Purpose: To analyze the influence of service quality dimensions on BPJS inpatient satisfaction. Method: A quantitative study with a cross-sectional design was conducted in the inpatient wards of Raden Mattaher Hospital in 2025. A total of 424 BPJS inpatients were selected using purposive sampling. Data were collected using a SERVQUAL-based Likert questionnaire covering tangibles, reliability, responsiveness, assurance, and empathy. Data were analyzed using univariate, bivariate (simple linear regression), and multivariate (multiple linear regression) analysis with SPSS at α=0.05. Results: Most respondents rated service quality as good (58.3%). The mean satisfaction score was 79.10±12.71. Partially, reliability (p=0.048) and assurance (p=0.000) significantly influenced satisfaction, while tangibles (p=0.312), responsiveness (p=0.087), and empathy (p=0.421) were not significant. Simultaneously, all dimensions significantly affected satisfaction (p=0.000) with R²=0.106. Assurance was the dominant factor (β=1.238). Conclusion: Service quality significantly influences BPJS inpatient satisfaction, with assurance as the strongest determinant. Strengthening professional competence and patient trust is essential to improve satisfaction levels. Keywords: BPJS; Inpatient; Patient Satisfaction; SERVQUAL; Service Quality.